Numerical Method for Modeling the Turbofan Engine Tonal Fan BPF Noise Generation and Propagation Accounting the SAS Complex Acoustic Impedance - F. Timushev, Sergey; N. Gavrilyuk, Vladimir; A. Aksenov, Andrey; A. Kharchenko, Sergey (International Journal of Engineering and Technology, 2018)
Noise reduction issues in the developed world receive an increasing attention, which is reflected in a great tightening of the noise level requirements. For the practical solution of this problem authors propose a new high-performance numerical modeling method of three-dimensional tonal noise acoustic field generated by the fan as a bladed machine. The method is based on solving a boundary value problem for Fourier transformed convective wave equation with complex variables in a Cartesian coordinate system in the arbitrary domain with impedance boundary conditions by finite volume method. The noise source is set in the form of sound power on the surface near the rotor that bounds the area of the vortex perturbations (pseudosound). Sound power is determined by acoustic-vortex method. There are shown examples of the method validation and application.Â Â